2007
DOI: 10.1111/j.1365-2605.2007.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake by mitochondria in demembranated human spermatozoa: a reliable tool for the evaluation of sperm respiratory efficiency

Abstract: In this work we report a relatively simple and fast method for analysing oxygen consumption and therefore mitochondrial functionality, in individual human ejaculates. This oxygraphic method requires a low number of cells, is highly reproducible and linearly correlates with sperm concentration. Our results have shown that oxygen uptake by mitochondria of demembranated sperm cells from normozoospermic subjects is significantly stimulated by a large set of respiratory substrates and ADP. The respiratory control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 23 publications
(39 reference statements)
8
61
1
Order By: Relevance
“…However, Narisawa et al [78] demonstrated that if this pathway is defective in mice, fertilization is not altered, and motility is reduced, but not suppressed. Furthermore, Ferramosca et al [79] suggest that mitochondrial oxygen uptake during respiration may be correlated with sperm DNA integrity, which can be supported by our results, because this pathway was not observed in the High sperm DNA fragmentation group. The exclusive protein Solute Carrier Family 2, facilitated glucose transporter member 14 (SLC2A14), and the overexpressed protein Phosphoglycerate Kinase 2 (PGK2) were related to these processes and previously suggested as fertility biomarkers by Kovac et al [40].…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupsupporting
confidence: 80%
“…However, Narisawa et al [78] demonstrated that if this pathway is defective in mice, fertilization is not altered, and motility is reduced, but not suppressed. Furthermore, Ferramosca et al [79] suggest that mitochondrial oxygen uptake during respiration may be correlated with sperm DNA integrity, which can be supported by our results, because this pathway was not observed in the High sperm DNA fragmentation group. The exclusive protein Solute Carrier Family 2, facilitated glucose transporter member 14 (SLC2A14), and the overexpressed protein Phosphoglycerate Kinase 2 (PGK2) were related to these processes and previously suggested as fertility biomarkers by Kovac et al [40].…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupsupporting
confidence: 80%
“…The mitochondrial sheath is organized in a helix of about 13 gyres, with two mitochondria per gyre, surrounding the axoneme at the midpiece level. Mitochondrial dysfunction is an important contributor to male infertility, including AS (Ferramosca et al 2008). Recently, it has been demonstrated that a subpopulation of human spermatozoa showing better fertilization potential is characterized by high mitochondrial functionality (Sousa et al 2011).…”
Section: Park7 Translocates Into the Damaged Mitochondria To Rescue Tmentioning
confidence: 99%
“…Several glycolytic enzymes have been identified mainly in the fibrous sheath of the principal piece in mammalian species (11). Because OXPHOS yields more ATP per mol of glucose than glycolysis, mitochondria are abundant in the mid-piece of mammalian sperm and may use a widerrange of substrates (fatty acids, monocarboxylic acids, and amino acids); respiration has been historically regarded as the main source of ATP production for sperm motility, relegating glycolysis to a secondary role (12)(13)(14)(15). However, there is a wide range of variation among mammalian species with regard to the primary mechanism for ATP production.…”
mentioning
confidence: 99%